2004
DOI: 10.1038/sj.onc.1207277
|View full text |Cite
|
Sign up to set email alerts
|

Gene array analysis of macronodular adrenal hyperplasia confirms clinical heterogeneity and identifies several candidate genes as molecular mediators

Abstract: Corticotropin (ACTH)-independent macronodular adrenal hyperplasia (AIMAH) is a heterogeneous condition in which cortisol secretion may be mediated by gastrointestinal peptide (GIP), vasopressin, catecholamines and other hormones. We studied the expression profile of AIMAH by genomic cDNA microarray analysis. Total RNA was extracted from eight tissues (three GIP-dependent) and compared to total RNA obtained from adrenal glands from 62 normal subjects. Genes had to be altered in 75% of the patients, and be up-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 64 publications
9
62
0
2
Order By: Relevance
“…They identified two clusters of genes, the IGF2 cluster and the steroidogenesis cluster, which, in combination, provide a good predictor of malignancy. As in our studies, they also confirmed the finding from the earlier analysis by Giordano et al (19) demonstrating upregulation of IGF2 expression (30). Adrenal hyperplasia was analyzed in a similar fashion by Bourdeau et al (30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They identified two clusters of genes, the IGF2 cluster and the steroidogenesis cluster, which, in combination, provide a good predictor of malignancy. As in our studies, they also confirmed the finding from the earlier analysis by Giordano et al (19) demonstrating upregulation of IGF2 expression (30). Adrenal hyperplasia was analyzed in a similar fashion by Bourdeau et al (30).…”
Section: Discussionsupporting
confidence: 82%
“…During the course of our studies, three other groups performed similar analyses of adrenocortical tissue (19,30,31). In the search for reliable markers for the clinical management of adrenal tumors, de Fraipont et al (31) designed an adrenal-specific microarray.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known by pathologists that follicular adenomas contain few lymphocytes and this decrease has been previously reported (Aust et al, 2001). A similar reduction has been described in the thyroids of Tg-A2aR mice (Goffard et al, 2004) and in the corresponding human adrenal disease, adrenal hyperplasia (Bourdeau et al, 2004). Decreased complement expression (C1s) extends this conclusion to macrophages.…”
Section: Discussionsupporting
confidence: 62%
“…According to another study on 33 patients from a single and large kindred of MEN1 (known as Tasman1), 2 The incidence of food-or GIP-dependent AIMAH is comparatively rare and has not been reported in familial cases of AIMAH [4][5][6]. In a microarray study of several types of AIMAH, analysis of gene expression profiles by hierarchical clustering revealed a distinct gene expression pattern in GIP-dependent AIMAH, which was different from that of non-GIP AIMAH [22]. This observation suggests that GIP-dependent AIMAH is fundamentally different from non-GIP AIMAH.…”
Section: Discussionmentioning
confidence: 99%